Ionospheric electron density profiling and modeling of COSMIC follow-on simulations - Tsai, L.-C.; Su, S.-Y.; Liu, C.H.; Tulasiram, S. (My University, 2015)
The FormoSat-3/ Constellation Observing System for Meteorology, Ionosphere and Climate (FS3/ COSMIC) has been proven a successful mission on pro- filing ionospheric electron density (Ne) using the radio occultation (RO) technique. A follow-on program (called FS7/COSMIC2) is now in progress. The FS3/COSMIC follow-on mission will have six 24◦-inclination and 550-km low Earth orbiting (LEO) satellites and six 72◦-inclination and 750-km LEO satellites to receive Tri-G (GPS, GLONASS, and Galileo) satellite signals. FS7/COSMIC2 RO observations were simulated in this study by calculating limbviewing GNSS-to-LEO TEC values separately through two independent ionospheric models (the TWIM and NeQuick models). We propose a compensatory Abel-inversion scheme to improve vertical Ne profiling and three-dimensional (3D) Ne modeling in this FS7/COSMIC2 simulation study with future real observations. In this FS7/COSMIC2 feasibility study the number of RO observations will increase of around 10 times compared with FS3/COSMIC, and the windowing day number to collect Ne profiles and to derive every half-hour 3D Ne model could be decreased from 30 to 3 days. The results show that the root-mean-square (RMS) foF2 and hmF2 difference improvements are 46% (32%) and 21% (4.6%), respectively, in relative percentage over the standard Abel inversion at the TWIM-background (NeQuickbackground) simulation experiment. The RMS modeling errors are about one order less than those from FS3/COSMIC simulations.
Keywords: Radio occultation observation; FS7/COSMIC2; Ionospheric Ne profiling; Ionospheric Ne modeling